Design and discovery of 3-aryl-5-substituted-isoquinolin-1-ones as potent tankyrase inhibitors1. Issue 9 (2nd September 2015) - Elliott, Richard J. R.; Jarvis, Ashley; Rajasekaran, Mohan B.; Menon, Malini; Bowers, Leandra; Boffey, Ray; Bayford, Melanie; Firth-Clark, Stuart; Key, Rebekah; Aqil, Rehan; Kirton, Stewart B.; Niculescu-Duvaz, Dan; et al.
<x xml:space="preserve">Abstract</x> The tankyrase proteins (TNKS, TNKS2) are attractive anti-cancer drug targets, particularly as inhibition of their catalytic activity has been shown to antagonise oncogenic WNT signalling.